Influence of match status and possession status on the physical and technical characteristics of elite youth female soccer match-play - Harkness-Armstrong, A.; Till, K.; Datson, N.; Emmonds, S. (Journal of Sports Sciences, 2023)
This study compared the influence of match status (drawing, losing, or winning) and possession status (in-possession, out-of-possession, or ball-out-of-play) on the physical and technical characteristics of U14 and U16 elite youth female soccer match-play. Data were collected from 189 female academy players during 45 competitive matches, resulting in 387 match observations. Linear mixed models estimated relative; total distance, high-speed running (=3.00 m·s-1), very high-speed running (=4.83 m·s-1), and sprinting (=5.76 m·s-1) distance according to match status and possession status, and 21 technical variables according to match status. Differences in physical and technical characteristics were observed between and within age-groups, dependent upon match status and possession status. Regardless of match status, both age-groups covered greater distances when the ball was in-play compared to ball-out-of-play (107-130 vs 58-68 m·min-1). U16s covered greater distances when out-of-possession than in-possession, regardless of match status. Whilst U14s covered greater distances out-of-possession when drawing or losing only. Differences in physical and technical characteristics when drawing, losing, or winning, suggest a change in playing style according to match status, likely in an attempt to influence or maintain the score-line. These findings have practical implications for coaching, talent identification and development practices within youth female soccer.